Online doctoral mentoring in a pandemic: help or hindrance to academic progress on dissertations? - Mullen, Carol A (International journal of mentoring and coaching in education, 2021)
PurposeThe author's purpose is to identify and analyze the progress of proposals and dissertations after mentor–mentee relationships rapidly transitioned to intensive online doctoral mentoring as a result of coronavirus 2019 (COVID-19).Design/methodology/approachAn exploratory pedagogic research design was implemented in 2020 to examine the COVID-19 Dyadic Online Mentoring Intervention, a four-month individualized approach to mentorship. A survey was completed by mentees in an educational leadership cohort that revealed the benefits and drawbacks of technology for learning within online doctoral mentoring contexts. Additional sources of data were published literature, mentor's notes, email exchanges, and scholarly enrichment products.FindingsData analysis yielded three themes: (1) mentoring strategies were utilized; (2) the pandemic unsettled reality and (3) personal professional development opportunities were evident. Although life challenges were exacerbated by the pandemic, the online doctoral mentoring intervention met dissertation-related needs and supported academic progress in a Doctorate in Education degree program.Practical implicationsTechnology-mediated mentoring during crises involves more than modality changes. Faculty mentors should not be solely responsible for mitigating program and dissertation disruption. Academic cultures must support the adoption of pedagogic innovations like high-quality online doctoral mentoring.Originality/valueOnline doctoral mentoring structures utilizing synchronous and asynchronous technologies can help mentees make academic progress in a crisis, not only in “normal” times.